The THE TRANSLATION METHOD WITH THE HELP OF MACHINE TRANSLATION ON AKU PENGGERAK MIMPI BY STUDENTS AT SMA SWASTA GKPI PADANG BULAN MEDAN : THE TRANSLATION METHOD WITH THE HELP OF MACHINE TRANSLATION ON AKU PENGGERAK MIMPI BY STUDENTS AT SMA SWASTA GKPI PADANG BULAN MEDAN - Sarinaiba Situmeang (Jurnal Scientia, 2022)
This study aims to analyze the translation method in the film Aku Penggerak Mimpi 2, using Machine Translation. This study is a qualitative approach conducted through descriptive research. The data used is a summary that will be made by students and will translate into English using machine translation through the Indonesian version of the film Aku Penggerak Mimipi 2. In data analysis by identifying methods based on Newmark. The results of this study reveal that the methods applied by translators are: word for word, faithful translation, semantic translation, idiomatic translation, free translation, communicative translation, and literal translation. There are 16 sentences used as data. The word for word is 3 sentences, idiomatic 5 sentences, faithful 2, literal 4, semantic 4 sentence, communicative 2 sentences, free translation 3 sentences. And from the results of research in 23 sentences, the author found that the translation method of idiomatic 5 translation found in 5 sentences is the one that is widely used by translators. This study only covers the translation method in the film "Aku Penggerak Mimpi 2 ". There are other fields of translation that can be used as a research center. Therefore, to complete the description of the translation of the film "Aku Penggerak Mimpi 2 ", other researchers are advised to conduct research. Others about this, such as the procedure translation, strategy and other areas of translation.